THE DYNAMICS RESEARCH AND TEST VERIFICATION BASED ON THE MISALIGNMENT OF THE HIGH-SPEED SHAFT - HU Yu Nong; ZHANG YueChun; WANG Wen; LI Min; ZHANG Yong (Jixie qiangdu)
Based on the misalignment of the high shaft,the paper puts forward an improved algorithm about the exciting force and torque generated by the coupling misalignment,which is under the influence of gyroscopic effect and inertial forces.Through the centralized mass method,the rotor system is simplified as a multi-disc system. According to the force balance and the coordination deformation motion system the establishment of the rotor of the differential equations,obtained exciting force and torque. N rotor systems are calculated the exciting force and torque caused by coupling misalignment via using the improved algorithm. According to the principles of probability and statistics,its characterization value can be got. Taking a high-speed flywheel housing for example,as a load is applied in a limited element dynamic simulation model carried harmonic response simulation,vibration test results with comparative analysis of the test results,which have been well validated,with a certain sense of engineering applications.